간호대학생의 좋은 죽음 인식과 임종간호태도가 공감역량에 미치는 영향 - 모서우; 방가영; 윤일훈; 문원희; Seo-U Mo; Ga-Young Bang; Il-hun Yoon; Weon-Hee Moon (미래기술융합논문지, 2024)
This study was a descriptive research study conducted to determine how nursing students' good death awareness and nursing attitudes toward dying patients affect their empathy. The subjects of the study were 155 nursing students, and data were collected using an online survey method. Data analysis was performed using descriptive statistics, independent t-test, one-way ANOVA, and multiple regression using the IBM SPSS Statistics 26. Higher attitude toward care of dying (B=.312) had a statistically significant positive effect on empathy capacity (p<.010). The variables that affected nursing students' empathy capacity were end-of-life experiences of relatives ( =.226) and attitude toward care of dying ( =.220). The regression model was statistically significant (F=6.968, p<.001), explained 10.4% of empathy. This study is expected to be used as basic data for the development of programs to strengthen the empathy capacity of nursing students in the future. 본 연구는 간호대학생의 좋은 죽음에 대한 인식과 임종환자에 대한 간호태도가 공감능력에 어떤 영향을 미치는지 알아보기 위해 실시한 서술적 조사연구이다. 연구대상자는 연구목적을 이해하고 참여에 동의한 간호대학생 155명으로, 온라인 설문조사법을 활용하여 자료를 수집하였다. 자료수집 기간은 2023년 4월 11일부터 총 34일이 소요되었다. 자료분석은 IBM SPSS Statistics 26 통계 패키지를 사용하여 기술통계, 독립 t-검정, 일원배치 분산분석, 다중회귀분석을 사용하여 수행되었다. 더미변수인 '지인의 죽음 경험'을 통제한 결과, 임종간호태도가 높을수록(B=.312) 공감능력에 통계적으로 유의한 긍정적인 영향을 미치는 것으로 나타났다(p<.01). 간호대학생의 공감능력에 영향을 미치는 변인은 지인의 임종경험( =.226), 임종간호태도( =.220)였으며, 회귀모형은 통계적으로 유의하였다(F=6.968, p<.001). 하나의 더미변수(지인의 임종경험)와 2개의 독립변수(임종간호태도, 좋은 죽임 인식)는 공감능력을 10.4% 설명하였다. 본 연구는 간호대학생의 공감능력에 미치는 영향을 분석함으로써 향후 간호대학생의 공감역량 강화를 위한 프로그램 개발의 기초자료로 활용될 수 있을 것으로 기대된다.